Multi-scale modelling approach for the pushover analysis of existing RC shear walls?Part I Model formulation. - Mulas, Maria Gabriella (Earthquake engineering & structural dynamics.)
This work focuses on the modelling issues related to the adoption of the pushover analysis for the seismic assessment of existing reinforced concrete (RC) structures. To this purpose a prototype reference structure, one of the RC shear walls designed according to the multi-fuse concept and tested on shaking table for the CAMUS project, is modelled at different levels of refinement. The meso-scale of a stiffness-based fibre element and the micro-scale of the finite element (FE) method are herein adopted; in the latter separate elements are adopted for the concrete, the steel and the steel?concrete interface. This first of the two companion papers presents in detail the wall under study, illustrating the design philosophy, the geometry of the wall, the instrumentation set-up and the test programme. The two modelling approaches are then described; the most important points in terms of element formulation and constitutive relations for materials are presented and discussed for each approach, in the light of the particular design of the wall and of its experimental behaviour.